Efektivitas Inovasi Aplikasi Absensi Berbasis Teknologi Dalam Menunjang Disiplin Kerja Pegawai Negeri Sipil Kepulauan Riau - Defany Ardianita; Novi Ramadhani; Ingrit Ramadhana Harifin (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
This study aims to analyze the effectiveness and influential factors in the application of technology-based attendance in supporting the work discipline of Civil Servants in Riau Islands. The research method used is descriptive research with a qualitative approach. The results showed that the application of technology-based attendance application innovation has significant effectiveness in improving the work discipline of Civil Servants. With the technology-based attendance application, the attendance process becomes more efficient and accurate. Employees can perform attendance quickly and easily through electronic devices such as smartphones or computers, without the need to use manual attendance that is prone to manipulation. In addition, factors that influence the effectiveness of technology-based attendance application implementation include management support, employee training, and employee awareness of the importance of work discipline. Strong management support in implementing and supervising the use of technology-based attendance applications is an important factor in successful implementation. Employee training in the use of the application is also key to ensuring proper and effective use. In addition, employee awareness of the importance of work discipline also plays a role in the successful implementation of this innovation. This research makes an important contribution to understanding the effectiveness of technology-based attendance application innovations in improving the work discipline of civil servants. The implication of this research is the importance of developing and implementing technological innovation in improving work efficiency and effectiveness in the public sector.